Design and Simulation of Infinite Impulse Response (IIR) Using the Impulse Invariant Method with Matlab Graphical User Interface (GUI) - Rusydi, Nauval (Journal of Electrical Engineering, Energy, and Information Technology (J3EIT), 2025)
Matlab is a software that is capable of performing calculations and simulations as well as developing applications based on Graphical User Interface (GUI). GUI-based application development can be done for digital signal processing, one of which is IIR digital signal filtering. The purpose of this research and development is to design a GUI to simulate an IIR digital filter. By entering the signal to be filtered and providing input parameter values in the form of filter type, filter order, cutoff frequency, passband ripple, and stopband ripple, the GUI will process the input values to filter the input signal given into an output in the form of a frequency spectrum. This GUI will be made stand-alone so that users do not need to open the Matlab application to use it. Testing for IIR digital signal filtering from the GUI is carried out by a digital filter verification test by comparing using various different cutoff frequencies, while maintaining other parameters where the results of the output signal have the same characteristics according to the filter. Then, to test the usefulness of each button, a blackbox test is carried out where the results obtained are that all buttons can work according to their respective functions without any problems or errors so that the resulting GUI can be used for IIR digital signal filtering. Then, for testing the GUI display, a survey was conducted on 30 respondents where the results had a value of 4.26 with the statement very satisfied.